Adjusment of Technology of Intensification Livestock at Area Rice Field Transmigration in South Konawe Regency - Hafid, Harapin (Journal of Saintech Transfer, 2021)
Transmigrant society generally have owned ox livestock and used as buffalo is livestock work to assist everyday them agricultural activity. But the way of conducted conservancy and conducting still have the character of traditional so that result of obtained not yet gratified, either from facet accretion of body wight and price sell yielded livestock. Conservancy facet and giving of feed, farmer still rely on to look for livestock forege at un-tilled areal which growed by many natural grasses, sometimes only given the rest of agricultural produce. Method approach of activity taken with: (1) discussion and discourse concerning activity livestock intensification technology, (2) tuition and demonstration election of seed, way of conducting, conservancy, preventive of disease and processing of result, (3) discussion and discourse concerning exploiting of agricultural produce remains as livestock pakan and processing of livestock dirt become compost. presented Counselling items get well enough and positive respon from all participants remember during the time have never been conducted similar activity. In general the participants wanted to adopt training materials and were very active in the demonstration of work livestock intensification techniques (80%) and 20% did not take a stand because farmers did not have cattle.. Please conclude that all targets which consist of all societies in of Cialam Jaya in activity of training applying of activity livestock intensification. All participants of wishful training to be their countryside is made by countryside of sercive Faculty of Agriculture University of Haluoleo in activity of devotion to society.